SEROLOGICAL VERUS HISTOLOGICAL DIAGNOSIS IN PEDIATRIC CELIAC DISEASE: IS THERE A NEED FOR SMALL BOWEL BIOPSY? - Aftab Anwar (Army Medical College Rawalpindi, 2021)
Objective: To evaluate the role of tissue transglutaminase IgA antibody (TTG IgA Ab) in diagnosis of pediatric celiac disease (CD) taking small bowel biopsy as gold standard.